2017
DOI: 10.1590/1983-80422017253216
|View full text |Cite
|
Sign up to set email alerts
|

Espiritualidade nos serviços de urgência e emergência

Abstract: There is a growing interest in the relationship between spirituality and the process of health and disease, due to the protection potential attributed to this dimension in difficult situations, such as during urgent and emergency care, which are identified as stress generators due to their characteristics. The aim of this study was therefore to evaluate how spirituality is addressed in urgency and emergency services. A review of literature from publications indexed in Medline and Scopus from 2000 to 2014 was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
(39 reference statements)
1
1
0
6
Order By: Relevance
“…Research among teachers concluded that there is a strong need to not only develop the competence of caring for the physical body in health students, but also the competence to care for the spirit. Therefore, this affirms that it is essential to incorporate spirituality in the undergraduate health curricula (25) .…”
Section: Category III -Undertaking Spiritual Care For the Hospitalizesupporting
confidence: 66%
“…Research among teachers concluded that there is a strong need to not only develop the competence of caring for the physical body in health students, but also the competence to care for the spirit. Therefore, this affirms that it is essential to incorporate spirituality in the undergraduate health curricula (25) .…”
Section: Category III -Undertaking Spiritual Care For the Hospitalizesupporting
confidence: 66%
“…A espiritualidade tende a ser um recurso importante para muitas famílias, podendo contribuir no enfrentamento aos desafios da vida, na adaptação e na resiliência às perdas (Walsh, 2016). Portanto, a espiritualidade costuma favorecer a maneira de lidar com situações adversas, como o luto, de modo que pode ser fortalecida nesse contexto (Biondo, Ferraz, Silva, & Yarid, 2017). Assim, nos casos em que a família menciona ter uma fé, estabelecida anteriormente à pandemia, é possível recomendar o contato virtual com líderes religiosos de referência (SSHAP, 2020), visando apoiar os enlutados em sua jornada espiritual na busca de maior significado e conexão (Walsh, 2016).…”
Section: Implicações Para a Prática De Psicólogos Diante Das Perdas Na Pandemia De Covid-19unclassified
“…A religiosidade refere-se à prática religiosa em si, em termos de frequência a templos ou cultos, por exemplo, mas também à execução dos rituais que constituem parte de determinada religião (3)(4) .…”
Section: Introductionunclassified
“…Os dados do 3° Levantamento Nacional sobre o Uso de Drogas pela População Brasileira (2015) evidenciaram que a prevalência de uso de substâncias alcóolicas (30%), tabaco (15%) e maconha entre a população é expressiva, com predomínio entre homens, adultos e jovens e, em menor proporção, cocaína (inalada), solventes e crack (8) relacionadas a usuários que vivem em precárias condições de vida e em situações de vulnerabilidade social (4)(5)(6)(7)(8) . Estudos evidenciaram que os jovens são os maiores consumidores dessas substâncias e que o uso vem ocorrendo cada vez mais cedo, associado a potenciais fatores de risco para diversos problemas sociais e de saúde sendo que dentre os principais fatores de proteção está a dimensão religiosa/espiritual (1)(2)(3)(4)(5) .…”
Section: Introductionunclassified
See 1 more Smart Citation